Dose-dense brentuximab vedotin plus ifosfamide, carboplatin, and etoposide for second-line treatment of relapsed or refractory classical Hodgkin lymphoma: a single centre, phase 1/2 study. Issue 8 (August 2021) - Lynch, Ryan C; Cassaday, Ryan D; Smith, Stephen D; Fromm, Jonathan R; Cowan, Andrew J; Warren, Edus H; Shadman, Mazyar S; Shustov, Andrei; Till, Brian G; Ujjani, Chaitra S; Libby, Edward N; Philip, Mary; et al.
Summary: Background: Relapsed or refractory classical Hodgkin lymphoma could be treated with multiagent salvage chemotherapy followed by autologous haematopoietic stem-cell transplantation. The aim of this study is to establish the safety and activity of dose-dense brentuximab vedotin combined with ifosfamide, carboplatin, and etoposide (BV-ICE) chemotherapy in second-line treatment of classical Hodgkin lymphoma. Methods: We conducted a single-arm, open-label, phase 1/2 study of dose-dense BV-ICE at the Seattle Cancer Care Alliance, University of Washington (Seattle, WA, USA). Eligibility criteria were age 18 years or older; diagnosis of first relapse, primary refractory classical Hodgkin lymphoma after one previous line of therapy; measurable disease of at least 1 cm in the longest axis, CT of chest, abdomen, and pelvis with PET within the past 28 days; Eastern Cooperative Oncology Group performance status of 0–1; and adequate organ function. A 3 + 3 dose escalation study was done for the phase 1 part of the trial to establish the maximum tolerated dose to be used for the phase 2 study. Brentuximab vedotin was delivered on days 1 and 8 at either 1·2 mg/kg (dose level 1) or 1·5 mg/kg (dose level 2) intravenously (capped at 150 mg) with standard dosing of ICE on days 1–3 (ifosfamide 5 g/m 2 plus mesna 5 g/m 2 intravenously over 24 h on day 2, carboplatin area under the curve 5 on day 2 in one intravenous injection, and etoposide 100 mg/m 2 on days 1–3 in one intravenous injection per day) for two 21-day cycles. The primary endpoint was to establish the recommended phase 2 dose (phase 1 part) and complete response rate after two cycles, with a prespecified target of 78% (phase 2 part). Safety analysis was done in all enrolled participants and the primary activity analysis was done in all patients with evaluable response data. This study is registered with ClinicalTrials.gov (NCT02227199); enrolment and study treatment are complete. Findings: Between Oct 16, 2014, and Feb 10, 2020, we enrolled 45 patients with a median age of 31 years (IQR 28–45). The recommended phase 2 dose of brentuximab vedotin was established to be 1·5 mg/kg. After a median follow-up of 3·1 years (IQR 1·7–4·1), 32 (74%; 95% CI 58·8–86·5) of 43 evaluable patients had complete responses after two cycles of treatment. Grade 3–4 haematological toxic effects were common, including neutropenia (33 [73%]), anaemia (six [13%]), and thrombocytopenia (36 [80%]). The most common grade 3–4 non-haematological toxic effects were febrile neutropenia (four [9%]), sepsis (six [13%]), increased alanine aminotransferase (five [11%]), hyperglycaemia (three [7%]), pulmonary embolism (two [4%]), and increased aspartate aminotransferase (two [4%]). There was one (2%) on-treatment death due to multisystem organ failure that was considered treatment related. Serious adverse events occurred in 13 (29%) patients. Interpretation: Our data suggest that dose-dense BV-ICE is a rapidly administered and active salvage regimen for patients with relapsed or refractory classical Hodgkin lymphoma despite a complete response in this trial lower than the prespecified phase 2 target. Although cross-trial comparisons should be made with caution, activity results seem to be similar to previously presented brentuximab vedotin chemotherapy salvage combinations delivered over much longer durations and can be considered in young (<60 years), transplantation-eligible patients for second-line therapy. Funding: Seagen, Lymphoma Research Foundation, National Institutes of Health/National Cancer Institute, and generous philanthropic donations to the University of Washington from numerous individuals and families in support of lymphoma research.